Analysis of the performance of coated carbide cutting tools in the machining of martensitic stainless steel aisi 410 in dry and mql conditions - De Paula, M. A. [UNESP]; Ribeiro, M. V. [UNESP]; Souza, J. V.C. [UNESP]; Kondo, M. Y. [UNESP] (IOP Publishing, 2019)
Stainless steels are widely used in industry because of their mechanical properties. Martensitic stainless steel AISI 410 is used in steam turbine blades, shaft and pump rotors, marine engine pistons, and components for petrochemical, food and pharmaceutical industries. Subjected to quenching and tempering, this material becomes harder and more resistant and, consequently, implies a greater wear of the cutting tools. The purpose of this work was to evaluate the performance of CVD (Chemical Vapor Deposition) and PVD (Physical Vapor Deposition) coatings in the turning of the martensitic stainless steel AISI 410 hardened under on dry and MQL (Minimum Quantity Lubrication) conditions. The cutting parameters used were: cutting speed (Vc = 125-150-175 m min -1 ), feed rate (f = 0.25 mm/rot) and depth of cut (ap = 0.5 mm). In the test conditions, the CVD coated carbide tools presented better results, as they did not present a break; while PVD coated carbide tools presented several breaks during turning. Scanning Electron Microscope (SEM) analyzes confirmed the occurrence of crater wear, chips and workpiece material adhered to the cutting tool. The use of the MQL technique was not satisfactory in the turning with the PVD tools and their coatings on it for these particular cutting conditions studied.
Keywords: machining; MQL; PVD and CVD coatings; roughness; stainless steels; wear